Construção de catálogo de meios para registrar e analisar as cargas de treinamento em tenistas de elite através do modelo de Planejamento, Registro e Análise da Carga de Treinamento (PRACTE) - Adolfo Emmanuel Nandayapa Jiménez (2020)
The aim of this study was to build a catalogue of group of training exercises for tennis, to record and analyze the training loads performed by elite tennis players during a microcycle in the pre-season period. The first phase consisted of building the catalogue of group of training exercises through literature review and classifying them in three dimensions by their specificity: General Training Exercises Group, Orientated Training Exercises Group and Special Training Exercises Group. In the second phase, was observed the training of 4 male tennis players national ranked within the first 20 and among the best 500 ATP ranked. Four video cameras Go-Pro HERO 5® were used to record all training sessions during microcycle on pre-season. Notational analysis was used to record effective training time and total duration training by using software KINOVEA® 0.8.27 version. Special Training Exercises were recorded using a registration form and tabulated data was organized using software Microsoft Office Excel 365®. The third phase consisted of analysis the Special Training Exercises Group trough the load parameters magnitude, structure and dynamics represented in absolute and percentage values for descriptive statistics. A total of 9 Special from 30 Training Exercises Groups that conformed this dimension were registered. The results regarding the magnitude parameter load showed agreement in relation to work:rest ratio for specific tennis literature highlighted (1:3). Trough the analysis of the magnitude and structure of the Special Exercises Training Groups was possible to identify the existing differences between hard court and clay court surfaces, influencing the effective training load duration time. Finally, differences were observed in the training of the 4 tennis players among the week by dynamic load parameter. Thus, the building of catalogue of training exercises for tennis showed that it can be a useful tool and in addition to contributing to the record an analysis training process, it can be used by coaches to planning the sport training loads.